Socio-family Factors Predictive of Adaptative Coping Post COVID-19 Pandemic in Nursing Students from a Private University - Velásquez Restrepo, Luz Enith; Basto Hernández, Gladys Judith; Muñoz Astudillo, María Nelcy (Investigación y Educación en Enfermería, 2023)
Objective. To identify socio-academic and family functionality factors – communication, cohesion, and flexibility – as predictive stimuli of adaptive coping of nursing university students in the post-COVID-19 pandemic. Methods. A cross-sectional descriptive study with stratified random sampling, with participation by 416 Nursing students from a private university in Pereira (Colombia), who answered a self-completed sociodemographic characterization survey, the Olson et al., communication scale, FACES III scale to assess family cohesion and flexibility, and the Calixta Roy CAPS scale to assess coping and adaptation capacity. Binary logistic regression and Hosmer-Lemeshow goodness-of-fit were performed to determine predictors of success, using SPSS v.26. Results. The profiles of the participants showed a higher proportion of women (78.4%), ages between 21 and 30 years (57.5%), young people who study and work (60.1%), and those who have an academic session on Friday and Saturday (67.5%). Nursing students perceive that their families communicate efficiently and satisfactorily (85.8%), have strong cohesion with a tendency towards attachment (73.6%) and flexibility, show a tendency towards chaos (70.7%) and have adaptive coping (48.5%). The success predictors for adaptive coping were female sex (p=0.007), academic session Friday and Saturday (p=0.042), occupation, study, and work (p=0.026), socioeconomic strata 4.5 and 6 (p=0.041), good or very good communication (p=0.001), balanced family cohesion (p =0.048), and balanced family flexibility (p=0.039). Conclusion. This study found that good family functionality and having adequate socioeconomic conditions were predictors of higher coping and adaptation capacity during the COVID-19 pandemic in the nursing students who participated in the study.